2021
DOI: 10.3390/languages6040203
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perceptions of Involvement in the Assessment of Oral Competence in English as a Second Language

Abstract: This mixed-method study examined students’ perceptions of involvement in the assessment practice of oral competence in English in Norwegian upper secondary schools. Student involvement in assessment can be seen as a key factor when it comes to enhancing students’ learning outcome and motivation. Previous research has, however, shown that student involvement and the assessment of oral competence in English as a second language classes have been challenging. Surveys (N = 116) and two focus group interviews (N = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Indeed, as has also been pointed out in the literature, the implementation of SA needs time and effort to be effective (e.g., Sandvik & Sommervold 2021).…”
Section: Agency Srl and Fa: Theoretical And Empirical Perspectivesmentioning
confidence: 93%
See 3 more Smart Citations
“…Indeed, as has also been pointed out in the literature, the implementation of SA needs time and effort to be effective (e.g., Sandvik & Sommervold 2021).…”
Section: Agency Srl and Fa: Theoretical And Empirical Perspectivesmentioning
confidence: 93%
“…Several studies have reported that SA strategies may be helpful for developing learner autonomy and, therefore, beneficial for learning (e.g., Andrade, 2010;Andrade & Brookhart, 2020). However, although several studies indicate positive effects of the use of SA to promote learners' oral language skills (e.g., Andrade, 2010), there are some concerns regarding the use of SA, and teachers and students are not always convinced of their usefulness (e.g., Oscarson & Apelgren, 2011;Sandvik & Sommervold, 2021). Since teacher beliefs are important when implementing tools in the classroom, this can affect the efficacy of the method.…”
Section: Agency Srl and Fa: Theoretical And Empirical Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, the assessment practices carried out by teachers also do not support the implementation of AaL in the classroom (Yildirim & Biliċan-Demiṙ, 2022). However, students actually want to be directly involved in the assessment process to improve their skills (Sandvik & Sommervold, 2021). This shows the teacher's perception of AaL as less important in assessment practice even though there is a desire to apply it during the learning process among students.…”
Section: Relationship Between Assessment Paradigm and Importance Of A...mentioning
confidence: 99%